THE ROLE OF P4S PERMATA HIJAU IN INCREASING HORTICULTURAL FARMERS' PRODUCTION AND INCOME IN NOELBAKI VILLAGE, CENTRAL KUPANG DISTRICT, KUPANG REGENCY - Katarina Desi; Charles Kapioru; Jullyo Gideon Rohi; Lika Bernadina (Buletin Ilmiah Impas, 2026)
Pusat Pelatihan Pertanian dan Perdesaan Swadaya (P4S/The Self-Help Agricultural and Rural Training Center) is a farmer-based institution that plays a role in improving farmers' capacity, production, and income. This study aims to analyze the role of P4S Permata Hijau as a facilitator and mediator, calculate horticultural farm income, and examine the relationship between the role of P4S and farmers' production and income in Noelbaki Village, Central Kupang District, Kupang Regency. The research method used was descriptive quantitative with a census technique involving 33 farmer members of P4S. Data were analyzed using a Likert scale, farm income analysis, and the Spearman Rank correlation test. The results show that the role of P4S Permata Hijau is categorized as highly influential, with a score of 83.84%. Horticultural farming, including chili, tomato, watermelon, and melon, generates high income and is feasible to develop, with chili being the most profitable commodity. The correlation test indicates that the facilitator role has a very strong and significant positive relationship with production and income (rs = 0.819; Sig. < 0.05), while the mediator role has a strong and significant positive relationship (rs = 0.626; Sig. < 0.05). In conclusion, P4S Permata Hijau plays an important role in increasing farmers' production and income and supports the development of more productive and sustainable horticultural farming.